2018
DOI: 10.3390/ijerph15102172
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Electronic Vape Exposure from Four Different Generations of Electronic Cigarettes: Airborne Particulate Matter Levels

Abstract: Electronic cigarettes (e-cigs) were introduced into the market in 2006 and their technological features have evolved substantially over time. Currently, there are four different generations of e-cigs that are broadly considered less harmful than the use of combusted tobacco products although passive exposure to aerosols often occurs in public spaces and indoor environments. The study aim was to evaluate the levels of airborne particulate matter (PM) emitted during the use of all the four generations of e-cigs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 29 publications
(31 reference statements)
2
56
0
2
Order By: Relevance
“…are One of its main air pollutants is airborne particulate matter (PM), comprising small particles consisting of solid and liquid droplets; of these, the most adverse health effects are associated with the inhalation of those of the PM10 size fraction and fractions with lower aerodynamic diameters. It has been found that during use, e-cigarettes produce PMs and moreover PM10 was almost made of PM1 size fraction [3]. There confirm other findings suggesting that e-cigarettes emit PM10, VOCs, nicotine and definitely impair air quality [211].…”
Section: Environmental Impact Of E-cigarettessupporting
confidence: 60%
See 1 more Smart Citation
“…are One of its main air pollutants is airborne particulate matter (PM), comprising small particles consisting of solid and liquid droplets; of these, the most adverse health effects are associated with the inhalation of those of the PM10 size fraction and fractions with lower aerodynamic diameters. It has been found that during use, e-cigarettes produce PMs and moreover PM10 was almost made of PM1 size fraction [3]. There confirm other findings suggesting that e-cigarettes emit PM10, VOCs, nicotine and definitely impair air quality [211].…”
Section: Environmental Impact Of E-cigarettessupporting
confidence: 60%
“…Although their initial inception dates back to 1963, the design of e-cigarettes in 2003 by Hon Lik, has spurred increasing global sales, which now show profits worth billions of dollars. Their popularity among the smoking community has also grown exponentially to the extent that e-cigarettes have become a leading product among the various alternatives to traditional cigarettes [1][2][3][4]. They comprise a battery-charged system containing a power source, a heater and a cartridge containing a liquid which transforms into vapor.…”
Section: Introductionmentioning
confidence: 99%
“…These devices were introduced for the first time into the market in 2006 and, since then, their features changed noticeably. To date, there are four different generations of e-cigs according to their technological characteristics: from the first (the simplest type) to the fourth generation (the most complex type), characterized by the possibility of modifying the operating power [2].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the possible adverse effects for active smokers of EATCs (the so-called vapers), experimental evidences demonstrate that the use of these devices worsen indoor air quality determining a typical passive exposure also called Environmental Electronic Vape (EEV) exposure [16][17][18]. The results of our previous researches [2,[19][20][21] highlighted that EEV exposure to particulate matter (PM) always occurs when e-cigs are used in indoor settings. This finding is not negligible in terms of public health as PM, independently from its composition, is a well-known risk factor for human health.…”
Section: Introductionmentioning
confidence: 99%
“…Vehicular traffic is the main source of UFPs in urban area [15][16][17][18]. In indoor settings, UFPs are released by devices and appliances commonly used (conventional and electronic cigarettes, electric appliances, etc) or activities usually practiced (cooking) [19][20][21][22][23][24]. In the last years more attention was given to indoor air quality, because great part of general population spends most of the time (> 90%) in enclosed environments [25] and indoor air may be of worse quality than outdoor, since indoor air pollutants are the sum of those penetrated from outdoor and those directly produced indoor [26,27].…”
Section: Introductionmentioning
confidence: 99%